2010
DOI: 10.7863/jum.2010.29.8.1153
|View full text |Cite
|
Sign up to set email alerts
|

Varicocele and Nutcracker Syndrome

Abstract: Abbreviations AMP, aortomesenteric portion; ANOVA, analysis of variance; LRV, left renal vein lthough the causes of infertility in men are of various characters and origins (eg, developmental defects and exposure to harmful agents), a substantial proportion, especially secondarily infertile men, have the clinically detectable and correctable vascular abnormality varicocele.Despite various theories, the underlying cause of varicocele remains enigmatic. The role of intrinsic anatomic differences between the left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
3
18
0
1
Order By: Relevance
“…An unusual manifestation of the nutcracker syndrome includes varicocele formation and varicose veins in the lower limbs (26). Another study has shown that the nutcracker syndrome is a frequent finding in varicocele patients (27), so it should be routinely searched in cases with left varicocele.…”
Section: Discussionmentioning
confidence: 99%
“…An unusual manifestation of the nutcracker syndrome includes varicocele formation and varicose veins in the lower limbs (26). Another study has shown that the nutcracker syndrome is a frequent finding in varicocele patients (27), so it should be routinely searched in cases with left varicocele.…”
Section: Discussionmentioning
confidence: 99%
“…However, the diagnostic procedure considered that the reference standard for establishing the diagnosis of NCS is invasive selective left renal phlebography with measurement of the pressure gradient between the LRV and inferior vena cava (1, 6, 10). Retrograde phlebography and cine video-angiography with reno-caval pressure gradient determination is accepted as the gold standard in establishing the final diagnosis of NCS.…”
Section: Discussionmentioning
confidence: 99%
“…In the differential diagnosis of NCS and accompanying pelvic congestion syndrome, pathologies that cause pain and hematuria such as lithiasis, congenital vascular malformations, tumors, infections, parenchymal or urinary tract abnormalities, painful pelvic syndromes and organ or neighboring structure alterations must be excluded (6, 10). Supportive treatment is adequate if the symptoms are mild in NCS.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all cases of RCC metastasis to the spermatic cord have occurred ipsilaterally on the left side, except for 2 case reports of contralateral RCC metastasis [ 8 , 9 ] . The anatomic differences between the left and the right renal vein drainage systems likely explain this [ 10 ] . Spermatic cord involvement by RCC can be either asynchronous or metachronous [ 11 ] .…”
Section: Discussionmentioning
confidence: 99%